Chronic Fragmentation of the Daily Sleep-Wake Rhythm Increases Amyloid-beta Levels and Neuroinflammation in the 3xTg-AD Mouse Model of Alzheimer's Disease. (15th January 2022) - Duncan, M.J.; Guerriero, L.E.; Kohler, K.; Beechem, L.E.; Gillis, B.D.; Salisbury, F.; Wessel, C.; Wang, J.; Sunderam, S.; Bachstetter, A.D.; O'Hara, B.F.; Murphy, M.P.
Highlights: Four daily bouts of exposure to novelty and gentle stimulation fragment the daily sleep-wake rhythm in female 3xTg-AD mice. Chronic fragmentation of the daily sleep-wake rhythm for four weeks increases hippocampal amyloid-beta accumulation. Chronic fragmentation of the daily sleep-wake rhythm also stimulates hippocampal neuroinflammation. The cortex does not exhibit sleep fragmentation-induced effects on amyloid-beta or neuroinflammation. These findings elucidate the correlation in humans between daily sleep-wake fragmentation and Alzheimer's disease risk. Abstract: Fragmentation of the daily sleep-wake rhythm with increased nighttime awakenings and more daytime naps is correlated with the risk of development of Alzheimer's disease (AD). To explore whether a causal relationship underlies this correlation, the present study tested the hypothesis that chronic fragmentation of the daily sleep-wake rhythm stimulates brain amyloid-beta (Aβ) levels and neuroinflammation in the 3xTg-AD mouse model of AD. Female 3xTg-AD mice were allowed to sleep undisturbed or were subjected to chronic sleep fragmentation consisting of four daily sessions of enforced wakefulness (one hour each) evenly distributed during the light phase, five days a week for four weeks. Piezoelectric sleep recording revealed that sleep fragmentation altered the daily sleep-wake rhythm to resemble the pattern observed in AD. Levels of amyloid-beta (Aβ40 and Aβ42 ) determined by ELISA were higher in hippocampal tissue collected from sleep-fragmented mice than from undisturbed controls. In contrast, hippocampal levels of tau and phospho-tau differed minimally between sleep fragmented and undisturbed control mice. Sleep fragmentation also stimulated neuroinflammation as shown by increased expression of markers of microglial activation and proinflammatory cytokines measured by q-RT-PCR analysis of hippocampal samples. No significant effects of sleep fragmentation on Aβ, tau, or neuroinflammation were observed in the cerebral cortex. These studies support the concept that improving sleep consolidation in individuals at risk for AD may be beneficial for slowing the onset or progression of this devastating neurodegenerative disease.